Analysing the rural B40 society in the microcredit programmes of Amanah Ikhtiar Malaysia (AIM). - Abdul Aziz, Mohamed Shamir; Asmawi, M. Zainora; Mahamod, Lukman Hakim (Secholian Publication, 2022)
The term microcredit finance refers to the provision of access to various financial services such as credit, savings, micro insurance, remittances as well as leasing to the poor or the low-income households. The purpose is to allow them to grow and support their small-sized businesses and eventually increase their level of income and standard of living. This study is about the methods of developing a framework for rural community that is categorised as B40 society to elevate their household income from the perspective of AIM members or formally called Sahabat. AIM provides small scale financial services and trainings to the poor and hard core poor households to improve their socio-economic conditions. Thus, the objective of this study is to assess the economic level and needs of Sahabat of AIM who are categorized as B40 rural society and to propose a sustainable microcredit conceptual framework for them. One major finding is that, majority of the respondents has quite high range of monthly expenditure and their monthly income is insufficient to cover their expenses. Even though majority of the respondents used the loans for business purposes, but there are still some respondents who used the loans for purposes other than business such as for food supply, health as well as education purposes. While majority of the respondents had received trainings from AIM, they realized that the programme held were still inadequate and the diversity of programme and trainings should be increased in accordance with the challenges they are facing today.